Heat Transfer Enhancement in a Heat Exchanger Tube with 45 Rectangular-Winglet Pairs - P. Tongyote; S. Sripattanapipat; P. Promvonge (My University, 2019)
An experimental investigation on thermal characteristics in a heat exchanger equipped with 45° rectangular winglet pairs (RWP) is conducted using air flowing in a constant heat flux tube with Reynolds number (Re) in a range of 5,200 to 23,000. Parameters of RWP included three relative height or blockage ratios (BR = 0.06, 0.08 and 0.1) and two pitch-spacing ratios (PR = 1.0 and 2.0). The heat transfer and the pressure drop in the test tube are displayed in the form of Nusselt number (Nu) and friction factor (f), respectively. The investigation shows that Nu and f values of the tube with RWP insert are, respectively, in the range of about 1.55−3.2 and 3.76−6.44 times above the plain tube alone, depending on the operating condition. The maximum thermal performance for using the RWP is found to be 1.7 at the lowest Re.
Keywords: Wingtip device; Heat Transfer Mechanisms